Classification of progressive banking products in optimal ranges in order to create of banking product-transformer for increasing efficiency of banking activity - E. V. Boganova (Путеводитель предпринимателя, 2020)
The article deals with conditions and methodological fundamentals for creating optimal range of progressive banking products related to these issues as well as trends in the development of progressive banking products in the banking sector of Russia